Exercise medicine and physical activity promotion: core curricula for US medical schools, residencies and sports medicine fellowships: developed by the American Medical Society for Sports Medicine and endorsed by the Canadian Academy of Sport and Exercise Medicine. Issue 7 (10th January 2022) - Asif, Irfan; Thornton, Jane S; Carek, Stephen; Miles, Christopher; Nayak, Melissa; Novak, Melissa; Stovak, Mark; Zaremski, Jason L; Drezner, Jonathan
Abstract : Regular physical activity provides a variety of health benefits and is proven to treat and prevent several non-communicable diseases. Specifically, physical activity enhances muscular and osseous strength, improves cardiorespiratory fitness, and reduces the risk of hypertension, coronary heart disease, stroke, type 2 diabetes, mental health disorders, cognitive decline and several cancers. Despite these well-known benefits, physical activity promotion in clinical practice is underused due to insufficient training during medical education. Medical trainees in the USA receive relatively few hours of instruction in sports and exercise medicine (SEM). One reason for this shortage of instruction is a lack of curricular resources at each level of medical education. To address this need, the American Medical Society for Sports Medicine (AMSSM) assembled a group of SEM experts to develop curricular guidance for exercise medicine and physical activity promotion at the medical school, residency and sports medicine fellowship levels of training. After an evidence review of existing curricular examples, we performed a modified Delphi process to create curricula for medical students, residents and sports medicine fellows. Three training level-specific curricula emerged, each containing Domains, General Learning Areas, and Specific Learning Areas; options for additional training and suggestions for assessment and evaluation were also provided. Review and comment on the initial curricula were conducted by three groups: a second set of experts in exercise medicine and physical activity promotion, sports medicine fellowship directors representing a variety of fellowship settings and the AMSSM Board of Directors. The final curricula for each training level were prepared based on input from the review groups. We believe enhanced medical education will enable clinicians to better integrate exercise medicine and physical activity promotion in their clinical practice and result in healthier, more physically active patients.